Photovoltaic performance of eutectic ionic liquids as potential electrolytes in dye-sensitized solar cells - Hilmy, N.I.M.F. (Elsevier Ltd, 2022)
Ionic liquids (ILs) have been utilized as the electrolyte in dye-sensitized solar cells (DSSCs) to replace organic solvents due to their non-flammability, chemical and thermal stability, as well as less tendency to evaporate and causing leakage. Herein, we report the photovoltaic performance of dye-sensitized solar cells for novel organic solvent-free eutectic ionic liquids (ILs) mixture as potential electrolytes in dye-sensitized solar cells (DSSCs). Eutectic ionic liquid mixtures based on 1-ethyl-3-methylimidazolium iodide C2C1imI and 1-butylpyridinium iodide C4pyI were studied and further incorporated with triiodide providers namely iodine, I2, and tetrabutylammonium triiodide TBAI-I-I, as well as 1-butyl-3-methylimidazolium thiocyanate BMIMSCN to form nine electrolytes formulations and their photovoltaic performances were evaluated. The selection of suitable triiodide providers as well as the effect of concentrations were reported along with the effect of viscosity on the performances of the devices. The best performing device was exhibited by C2C1imI: C4pyI: I2 (5 wt%) with a short circuit current of 2.68 mA cmâ2, an open-circuit voltage of 0.43 V, and a fill factor of 0.44, corresponding to an overall power conversion efficiency (PCE) of 0.51% which shows their potentials for electrolyte application in dye-sensitized solar cells. Â© 2022